Stress and quality of life among mothers with Thalassemic children in Malaysia - Mohd Miskam, Hazlina; Juhari, Rumaya; Yaacob, Siti Nor (International Journal of Children, Women, Elderly and Disable People, 2017)
Mothers of Thalassemic children are often confronted with stressful life associated with the illness of the child as well as other related stressors. Consequently, these mothers’ quality of life is impacted. This is a cross-sectional study involving 372 mothers who have children with Thalassemia that undergo routine blood transfusions every month from ten government hospitals in Malaysia. Data collection consisted of face-to-face interviews using the Parental Stress Scale and SF 12v2. Medical Research Ethics Committee (MREC) ethical approval was obtained prior to conduct this study. Results indicated that the working mothers have a good quality of life compared to those who are not working. However, there are no differences in stress among mothers who are working and not working. Results also showed a significantly negative direction in the relationship between quality of life and stress (r = -0.269, p < 0.001). In summary, the findings from our study highlight the importance of coping strategies and the role of the healthcare team to develop intervention programs for decreasing stress levels and promoting better quality of life for mothers of Thalassemic children. In addition, issues and challenges faced by primary caregivers of Thalassemic children in Malaysia should be addressed.